Exploring agriscience - Herren, Ray V. (Albany : Delmar Publishers, 1997)
Introduces students to the industry of agriculture, covering such topics as plant structures, raising crops, livestock, and poultry, forest science, environmental protection, biotechnology, and more.
Includes index.
Keywords: Agriculture -- Juvenile literature; Agriculture